THE DIGITAL REVOLUTION OF ISLAMIC SOCIAL FINANCE: THE TRANSFORMATION OF ZAKAT, WAQF, AND FINTECH IN REALIZING SUSTAINABLE DEVELOPMENT GOALS IN INDONESIA - alfian, ian; Agustina, Surya; Nasution, Yenni Samri Juliati; Marliyah, Marliyah (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
This study aims to analyze the transformation of Islamic Social Finance in the digital era and the strategic role of the National Committee for Islamic Economics and Finance (KNEKS) in strengthening the Islamic social finance ecosystem in Indonesia. The method used is a Systematic Literature Review (SLR) based on the PRISMA protocol, which includes the process of identification, selection, eligibility, and inclusion of scientific publications. A total of 25 selected articles published between 2019 and 2025 were analyzed using a thematic synthesis approach and quality assessment using the JBI Critical Assessment Tool. The research findings show that the digitization of Islamic Social Finance through fintech platforms, digital zakat wallets, digital waqf, and sharia crowdfunding has increased the efficiency of collection, transparency of distribution, and expanded access to services for the unbanked population. However, challenges remain in digital literacy, public trust, regulatory integration, and the readiness of the managing institutions' infrastructure. This study confirms that KNEKS plays a significant coordinating role in strengthening governance, standardizing policies, and integrating social finance systems with national development goals. The findings also show that Islamic Social Finance contributes to accelerating the achievement of the Sustainable Development Goals (SDGs), particularly poverty eradication, inclusive education, food security, and women's empowerment. The policy implications of this study include the need to improve digital and Sharia literacy, harmonize Sharia fintech regulations, and develop integrated digital platforms based on technologies such as blockchain and artificial intelligence to strengthen transparency and accountability.